Paul's thorn in the flesh: new clues for an old problem - Berding, Kenneth (Lexham Academic, 2023)
Paul's enigmatic "thorn in the flesh" in 2 Corinthians has baffled interpreters for centuries. Many offer suggestions as to the identity of Satan's messenger; others despair that the puzzle is unsolvable. In Paul's Thorn in the Flesh: New Clues for an Old Problem, Kenneth Berding reopens the case. He follows a trail of clues that includes ancient beliefs about curses, details from Paul's letters, Jesus's own suffering, and the testimony of the earliest Christian interpreters. Berding offers twenty criteria--some familiar, others neglected--that any proposal must explain. While the usual suspects fall short, Berding suggests a new solution--one that satisfies all the evidence and gives us a fuller view of Paul. Far from an abstract puzzle, Paul's own suffering is relevant to Christians today. Paul's Thorn in the Flesh is an accessible study that casts new light on Pauline studies, first--century background, and theological and pastoral concerns. --